Semen Analysis in Type 2 Diabetes Mellitus Patients with Infertility: Semen Analysis in Type 2 Diabetes Mellitus Patients with Infertility - Babu, K Ranjith; Manibalan, V; Bonam, Venkata Ramesh (Universitas Brawijaya, 2025)
Background: According to World Health Organization (WHO), the condition of infertility is related with inability to get conceived even after regular unprotected active sexual intercourse for one year. Nowadays, the prevalence of infertility is increasing day by day. Among couples who are desperate for pregnancy, about to 15% have complaints related to infertility. Aim: The present study is aimed to analyze and compare different semen parameters among diabetic infertile males and non-diabetic fertile males. Methods: This cross-section study done at Dr.Patnam Mahender Reddy Institute of Medical Sciences, Chevella and included 100 diabetic infertile and 100 fertile males. Subjects are selected as per inclusion and exclusion criteria. After 2 to 7 days of sexual abstinence, the semen samples were obtained by masturbation. Semen samples were then observed for microscopic and macroscopic examination as per WHO instructions. Blood sample was collected from a cubital vein, and serum was obtained. The results obtained were entered in tabular form with relevant heading of each parameter. The obtained data is analyzed IBM SPSS Statistics version 20. Results: It has been observed that there was a significant decrease of sperm concentration, sperm motility, sperm count, semen volume and sperm morphology in diabetic infertile group when compared to non-diabetic fertile group with significant increase in semen liquefaction time and appearance of abnormal sperms. Conclusion: Levels of Liquefaction time, abnormal appearance, viscosity and abnormal morphology were found to increased and sperm motility, concentration, count were observed to be decreased in the study group on comparison control group.